The Boss Is Back in Town: Insights into the Wolf Recolonization of a Highly Anthropized and Low-Ungulate-Density Environment - Lorenzo Frangini; Giacomo Marzano; Alice Comuzzi; Andrea De Giovanni; Andrea Gallizia; Marcello Franchini; Michela Rugge; Marco De Luca; Giuseppe De Matteis; Stefano Filacorda (Animals)
This study documents the recolonization of the wolf using opportunistic and systematic data, including camera trapping and scat surveys in south-eastern Italy. Wolf distribution was mapped using a 10 × 10 km grid, and Generalized Linear Models (GLMs) were applied to identify environmental and anthropogenic drivers of stable presence. Camera trapping and scat analyses were used to provide the first insights into the activity patterns and feeding habits of the species. The results showed a significant expansion in wolf range, with occurrence increasing by 120%, especially in areas with high forest cover. During 1402 camera-trap nights, wolves and wild prey species displayed primarily nocturnal activity, reducing overlap with human presence, though prey activity peaks were offset from those of wolves. Diet analysis of 75 scats revealed a high occurrence of livestock and pets, along with all wild species living in the area (i.e., ungulates, medium-sized and micromammals). These findings underscore the wolf’s ecological adaptability and ability to thrive in heavily altered landscapes. Indeed, this study shows how wolves were able to occupy even suboptimal areas, taking advantage of both anthropogenic and wild trophic resources, still displaying nocturnal activity to lower the probability of encounters with humans.